The Role and Importance of Outsourcing as a Modern Management Method in the Finance Sector on the Example of Own Research - Waldemar Kunzand Adam Döring (Communications of International Proceedings, 2025)
Today's businesses are facing dynamic creeds that require effective and innovative management approaches. In the area of today's global economy, the need to increase competitiveness, optimize costs and focus on core competencies raise questions for business management about optimal management strategies. Business management is a constant search for new management solutions, with the goal of increasing competitiveness and efficiency. Contacts between the organization and its partners consume a lot of resources, energy and attention. Modern market and environment with their requirements force organizations to respond expressly On the signals of these changes. The purpose of this article is to introduce the practical application of outsourcing as a modern management method. The main objective is to analyze outsourcing practices in the Polish context, identify the benefits, challenges and trends associated with outsourcing, and assess the impact of outsourcing on the efficiency and competitiveness of Polish companies. The study used a diagnostic survey method, with a survey technique and research tool of a survey questionnaire addressed to 460 respondents. The survey was based on six companies in the sector banking companies that include PKO Bank Polski, mBank, ING Bank Slaski, Pekao SA, Alior Bank and Getin Noble Bank. In order to identify the issue in more depth, the article additionally uses research methods consisting of both descriptive and comparative analysis of financial statements.
Keywords: Management; Banking; Finance; Outsourcing